Improvement of RG1-VLP vaccine performance in BALB/c mice by substitution of alhydrogel with the next generation polyphosphazene adjuvant PCEP. Issue 8 (3rd August 2021) - Valencia, Sarah M.; Zacharia, Athina; Marin, Alexander; Matthews, Rebecca L.; Wu, Chia-Kuei; Myers, Breana; Sanders, Chelsea; Difilippantonio, Simone; Kirnbauer, Reinhard; Roden, Richard B.; Pinto, Ligia A.; Shoemaker, Robert H.; et al.
ABSTRACT: Current human papillomavirus (HPV) vaccines provide substantial protection against the most common HPV types responsible for oral and anogenital cancers, but many circulating cancer-causing types remain for which vaccine coverage is lacking. In addition, all current HPV vaccines rely on aluminum salt-based adjuvant formulations that function through unclear mechanisms with few substitutes available. In an effort to expand the toolbox of available adjuvants suitable for HPV vaccines, we compared the immunogenicity of the RG1-VLP (virus-like particle) vaccine in BALB/c mice when formulated with either the aluminum hydroxide adjuvant Alhydrogel or the novel polyphosphazene macromolecular adjuvant poly[di (carboxylatoethylphenoxy) phosphazene] (PCEP). PCEP-formulated RG1-VLPs routinely outperformed VLP/Alhydrogel in several measurements of VLP-specific humoral immunity, including consistent improvements in the magnitude of antibody (Ab) responses to both HPV16-L1 and the L2 RG1 epitope as well as neutralizing titers to HPV16 and cross-neutralization of pseudovirion (PsV) types HPV18 and HPV39. Dose-sparing studies indicated that RG1-VLPs could be reduced in dose by 75% and the presence of PCEP ensured activity comparable to a full VLP dose adjuvanted by Alhydrogel. In addition, levels of HPV16-L1 and -L2-specific Abs were achieved after two vaccinations with PCEP as adjuvant that were equivalent to or greater than levels achieved with three vaccinations with Alhydrogel alone, indicating that the presence of PCEP resulted in accelerated immune responses that could allow for a decreased dose schedule. Given the extensive clinical track record of polyphosphazenes, these data suggest that substitution of alum-based adjuvants with PCEP for the RG1-VLP vaccine could lead to rapid seropositivity requiring fewer boosts, the dose-sparing of commercial VLP-based vaccines, and the establishment of longer-lasting humoral responses to HPV.